Word Of Mouth as Media - Luthfi Febri; Dadan Mulyana (UNISBA Press, 2022)
Abstract. The development in the culinary field is inseparable from the various changes in globalization factors through the internet which are the triggers, including the increasing emergence of various types of culinary from various countries as well as the expectations of consumers who want a form of culinary with the latest variety . And in this case, with the various business brands that have been circulating, a new business in the culinary field has emerged, namely a cereal shop called the Sunday Bowl Cereal Club. The unique thing Sunday Bowl about thiscase is that they are pioneers and within 1 year of their business journey they did not incur large marketing costs, they only maximized thestrategy word of mouth for their marketing communications, with this strategy they managed to become one of the sufficient food stalls. known in the city of Bandung. Research objectives to understand its promotion done by word of mouth sunday bowl, The a message from word of mouth on Sunday Bowl, why Sunday Bowl the media particular social on implementing a word of mouth. This research used the qualitative method, which is Robert K. Yin case study with type I research design that focused on a case with a unit of analysis using interviewees as the key informants of this research. Drawing conclusions: stage promotion word of mouth conducted by the Sunday Bowl identify activities communication word of mouth directly talked about the negative and positive services and products that is in a tavern Sunday Bowl. Message content promotion which is to create a rational and moral attraction. The reason the use of social media to simplify and accelerate the message information sunday bowl known by users social media as consumers target. Abstrak. Perkembangan di bidang kuliner tidak terlepas dari berbagai perubahan faktor globalisasi melalui internet yang menjadi pemicunya, di antaranya adalah meningkatnya kemunculan macam – macam jenis kuliner dari berbagai negara serta harapan konsumen yang menginginkan suatu bentuk kuliner dengan ragam terbaru. Dan dalam kasus ini dengan ragam merek usaha yang telah beredar munculah salah satu bisnis baru di bidang kuliner yaitu kedai sereal bernama Sunday Bowl Cereal Club. Hal unik dari kasus Sunday Bowl ini adalah dimana mereka adalah pionir dan dalam kurun 1 tahun perjalanan bisnisnya tidak mengeluarkan biaya marketing yang besar, mereka hanya memaksimalkan strategi word of mouth untuk komunikasi pemasaran mereka, dengan strategi tersebut mereka berhasil menjadi salah satu kedai makanan yang cukup dikenal di kota Bandung. Tujuan penelitian untuk mengetahui tahapan promosi word of mouth yang dilakukan oleh Sunday Bowl, isi pesan dari word of mouth pada Sunday Bowl, mengapa Sunday Bowl menggunakan media sosial tertentu dalam mengimplementasikan word of mouth. Metode penelitian kualitatif, studi kasus Robert K. Yin desain penelitian tipe 1 berfokus pada satu kasus dengan satu unit analisis menggunakan wawancara narasumber sebagai key informanpenelitian. Simpulan: tahapan promosi word of mouth yang dilakukan oleh Sunday Bowl yaitu mengidentifikasi kegiatan komunikasi word of mouth yang secara langsung membicarakan tentang nilai positif dan negatif pelayanan dan produk yang ada di kedai Sunday Bowl. Isi pesan promosi yaitu menciptakan daya tarik pesan rasional dan moral, Alasan penggunaan media sosial dapat mempermudah dan mempercepat pesan informasi Sunday Bowl diketahui oleh masyarakat pengguna media sosial sebagai konsumen target.